A return journey : hope and strength in the aftermath of Alzheimer's - Petrovski, Sue Matthews (Purdue University Press, 2017)
What choices were right, what choices were wrong, and how can she now help those whose journey is just beginning. She clearly and wisely explains that in Alzheimer's there are no right" ways, no "best" decisions, no "perfect" answers. The Return Journey is the result of Sue's personal journals during her mother's 8-year illness and her correspondence with other caregivers kind enough to share their innermost feelings and emotions. Their stories provide the reader with an insider's view - lessons to be learned from looking through the personal peephole of family members at the heart of the experience itself."